Assembly dynamics of a forest bird community depend on disturbance intensity and foraging guild. Issue 3 (15th September 2016) - Kroll, Andrew J.; Verschuyl, Jake; Giovanini, Jack; Betts, Matthew G.
Summary: Tree plantations occur globally and are often promoted as a strategy to supply wood products for an expanding human population while reducing pressure on natural forests. Herbicides can accelerate growth of crop trees by suppressing competing vegetation, but little information is available about potential trade‐offs with early seral biodiversity resulting from more intensive management. Using data collected over 5 years immediately following stand‐replacing disturbance (clear‐felling), we used a large‐scale experiment to test how environmental filtering influences dynamics of avian community assembly. We evaluated avian responses to three levels of plant cover reduction (light, moderate and intensive herbicide applications) in relation to a control without herbicide. Under the environmental filtering hypothesis, we expected reduced avian species richness and higher turnover as broadleaf plant cover decreases with increasing management intensity. We predicted that the most intensive treatments would exert strong negative effects on leaf‐gleaning insectivores, including several species of conservation concern due to long‐term population declines. Richness of leaf‐gleaning bird species was reduced by 23–52% over the 5 years on moderate (standard practice) vs. control treatments, but effects were substantially smaller for the non‐leaf‐gleaner guild in years 1–4 (8–25%) and disappeared by year 5 (0%). Both leaf‐gleaner and non‐leaf‐gleaner functional groups continued to colonize moderate and intensive treatments at higher probabilities than the control in Year 5 (range: 0·17–0·29), likely due to rapid vegetation recovery after herbicide applications ceased. Planted conifers were >35% taller and >70% larger in diameter in the two most intensive treatments, leading to substantially more wood volume produced per unit area than on stands without herbicide applications. Synthesis and applications . Under current management regimes, stand‐level trade‐offs between conservation of avian diversity and production of wood commodities may be less severe than previously recognized. However, in landscapes where biodiversity conservation rather than wood production is the primary goal, managers can adjust the trade‐off by making relatively small reductions in herbicide use that should have positive impacts on richness of leaf‐gleaning insectivorous birds. Abstract : Under current management regimes, stand‐level trade‐offs between conservation of avian diversity and production of wood commodities may be less severe than previously recognized. However, in landscapes where biodiversity conservation rather than wood production is the primary goal, managers can adjust the trade‐off by making relatively small reductions in herbicide use that should have positive impacts on richness of leaf‐gleaning insectivorous birds.